Genotoxicity Assessment Of Standardised Root Extract Of Eurycoma Longifolia Jack And Synthesis Of Some Benzimidazole Derivatives And Evaluation Of Their Anti-Cancer Potential - Muttiah, Nithya Niranjini (2013)
In this study, the genotoxic potential of standardised root extract, F2 of Eurycoma longifolia Jack has been assessed using the mouse lymphoma assay (MLA) in accordance with OECD guideline. This work serves to be the first test to evaluate the safety profile of E. longifolia using the in vitro mammalian system. The MLA is capable of detecting a broad spectrum of mutational events include point mutations and chromosomal abberations. The L5178Y/tk+/- cells were treated with 1 to 50 μg/mL of the root extract in the absence and presence of S9 metabolic activation for 3-h. A 24-h treatment assay was performed without the S9 metabolic activation.